Analysis of Banking Financial Performance Before and While the Pandemic Era Using Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) Method - Safira AM, Zia; Yuana, Pusvita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the level of bank soundness at PT Bank CIMB Niaga Tbk during the 2018-2021 period i.e 2 years before and 2 years while the pandemic era of COVID-19 using the RGEC method (Risk Profile, Good Corporate Governance, Earning, and Capital). This research is measured through several financial ratios, including NPL, LDR, GCG by Self-assessment, ROA, NIM, and CAR. This study uses a quantitative-descriptive type of research through secondary data obtained by the documentation method in the form of annual financial reports which are accessed through the official website of PT Bank CIMB Niaga Tbk and credible institutions. The results of this study indicate that the condition of PT Bank CIMB Niaga Tbk before and while the pandemic era of COVID-19 2018-2021 on average in risk profile with NPL got a level of 2 which means healthy. LDR was level 2 which means healthy, GCG got a level of 1 which means very healthy, earnings with ROA ranked as 2 which means healthy, NIM ranked as 1 which means very healthy, and capital with CAR ranked as 1 which means very healthy. All results generally obtained a composite level of 2 which means healthy. Although several aspects of the assessment were found with the soundness of the bank at the composite level of 3 during the pandemic of COVID-19, this did not affect the final result of the soundness of the bank.